A critical appraisal of evidence-and consensus-based guidelines for actinic keratosis - Wessely, Anja; Steeb, Theresa; Heppt, Franz; Hornung, Annkathrin; Kaufmann, Matthias; Koch, Elias; Toussaint, Frédéric; Erdmann, Michael; Berking, Carola; Heppt, Markus (Current Oncology, 2021)
Actinic keratoses (AK) are common lesions of the skin that can be effectively treated with several lesion-and field-directed treatments. Clinical practice guidelines assist physicians in choosing the appropriate treatment options for their patients. Here, we aimed to systematically identify and evaluate the methodological quality of currently available guidelines for AK. Guidelines published within the last 5 years were identified in a systematic search of guideline databases, Medline and Embase. Then, six independent reviewers evaluated the methodological quality using the tools “Appraisal of Guidelines for Research and Evaluation” (AGREE II) and “Recommendation EXcellence” (AGREE-REX). The Kruskal–Wallis (H) test was used to explore differences among subgroups and Spearman’s correlation to examine the relationship between individual domains. Three guidelines developed by consortia from Canada, Germany and the United Kingdom were eligible for the evaluation. The German guideline achieved the highest scores, fulfilling 65 to 92% of the criteria in AGREE II and 67 to 84% in AGREE-REX, whereas the Canadian guideline scored 31 to 71% of the criteria in AGREE II and 33 to 46% in AGREE-REX. The domains “stakeholder involvement“ and “values and preferences“ were identified as methodological weaknesses requiring particular attention and improvement in future guideline efforts.
CRIS-Team Scopus Importer:2021-04-02
Keywords: actinic keratosis; AGREE; Level of evidence; Practice guideline; Solar keratosis

Active vitamin D supplementation and COVID-19 infections: review - Farid, Nakhoul; Rola, Nakhoul; Koch, Elias; Nakhoul, Nakhoul (Irish Journal of Medical Science, 2021)
SARS-CoV-2, causing the lethal disease COVid-19, is a public health emergency in the 2020 global pandemic. The outbreak and fast spreading of SARS-CoV-2 have a high morbidity and mortality specifically in elder patients with chronic diseases such as diabetes mellitus, arterial hypertension, chronic kidney disease, and organ transplanted patients with immunosuppressive therapy. Preliminary results support different treatments such as chloroquine and convalescent plasma infusion in severe cases, with good outcome. On the other hand, the efficacy of supplementation with active vitamin D, an immunomodulator hormone with antiinflammatory and antimicrobial effects, is unproven. A recent study reported that vitamin D attains antiviral effects, via blocking viral replication directly. SARS-CoV-2 primarily uses the immune evasion process during infection via the envelope spike glycoprotein, which is followed by a cytokine storm, causing severe acute respiratory disease syndrome and death. SARS-CoV-2, by using the well-known angiotensin-converting enzyme 2 by the protein spike, as the host receptor to enter into alveolar, myocardial, and renal epithelial cells, can be disrupted by vitamin D. However, the correlation between vitamin D levels and COVID-19 deaths in previous studies was insignificant. Retrospective studies demonstrated a correlation between vitamin D status and COVID-19 severity and mortality, while other studies did not find this correlation. Studies have shown that, vitamin D reduces the risk of acute viral respiratory tract infections and pneumonia via direct inhibition of viral replication, antiinflammatory and immunomodulatory effects. The data available today regarding the beneficial protective effect of vitamin D is unclear and with conflicting results. Large randomized control trials are necessary to test this hypothesis. In this review, we will explain the cross talk between the active vitamin D and the angiotensin-converting enzyme 2, and summarize the data from the literature.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Angiotensin converting enzyme 2; COVID-19; Renin; SARS-CoV-2; Vitamin D

A One-Armed Phase I Dose Escalation Trial Design: Personalized Vaccination with IKKβ-Matured, RNA-Loaded Dendritic Cells for Metastatic Uveal Melanoma - Koch, Elias; Schaft, Niels; Kummer, Mirko; Berking, Carola; Schuler, Gerold; Hasumi, Kenichiro; Dörrie, Jan; Schuler-Thurner, Beatrice (Frontiers in Immunology, 2022)
Uveal melanoma (UM) is an orphan disease with a mortality of 80% within one year upon the development of metastatic disease. UM does hardly respond to chemotherapy and kinase inhibitors and is largely resistant to checkpoint inhibition. Hence, further therapy approaches are urgently needed. To improve clinical outcome, we designed a trial employing the 3rd generation personalized IKKβ-matured RNA-transfected dendritic cell (DC) vaccine which primes T cells and in addition activates NK cells. This ongoing phase I trial [NCT04335890 (www.clinicaltrials.gov), Eudract: 2018-004390-28 (www.clinicaltrialsregister.eu)] investigates patients with treatment-naive metastatic UM. Monocytes are isolated by leukapheresis, differentiated to immature DCs, matured with a cytokine cocktail, and activated via the NF-κB pathway by electroporation with RNA encoding a constitutively active mutant of IKKβ. Three types of antigen-RNA are co-electroporated: i) amplified mRNA of the tumor representing the whole transcriptome, ii) RNA encoding driver mutations identified by exome sequencing, and iii) overexpressed non-mutated tumor antigens detected by transcriptome sequencing. This highly personalized DC vaccine is applied by 9 intravenous infusions in a staggered schedule over one year. Parallel to the vaccination, standard therapy, usually an immune checkpoint blockade (ICB) as mono (anti-PD-1) or combined (anti-CTLA4 and anti-PD-1) regimen is initiated. The coordinated vaccine-induced immune response encompassing tumor-specific T cells and innate NK cells should synergize with ICB, perhaps resulting in measurable clinical responses in this resistant tumor entity. Primary outcome measures of this trial are safety, tolerability and toxicity; secondary outcome measures comprise overall survival and induction of antigen-specific T cells.
CRIS-Team Scopus Importer:2022-03-04
Keywords: IKKβ-matured dendritic cells; Immune checkpoint blockade; metastatic uveal melanoma; personalized vaccine; tumor antigen vaccine; tumor antigens

A Systematic Review and Meta-Analysis of Interventions for Actinic Keratosis from Post-Marketing Surveillance Trials - Steeb, Theresa; Wessely, Anja; Harla, Matthias; Heppt, Franz; Koch, Elias; Leiter, Ulrike; Garbe, Claus; Schöffski, Oliver; Berking, Carola; Heppt, Markus (Journal of Clinical Medicine, 2020)
Multiple interventions are available for the treatment of actinic keratosis (AK) showing high efficacy in pivotal trials. However, data from post-marketing surveillance studies have received little attention until now. Here, we systematically investigate interventions for AK from post-marketing surveillance trials as a proxy for real-world efficacy and tolerability. A systematic literature search was conducted in Medline, Embase, and CENTRAL. Pertinent trial registers were hand-searched until 25 March 2020. Results were pooled using a random-effects model to calculate pooled proportions and relative risks (RR) or were described qualitatively. Eleven records with a total sample size ofn= 4109 were included. Three of the studies had an active-controlled design, while seven were single-armed. Participant complete clearance ranged from 23.1% for diclofenac sodium 3% gel to 88.9% for ingenol mebutate 0.05% gel. The lesion-specific clearance rate for photodynamic therapy (PDT) was 74% (95% confidence interval (CI) 56-87%). The recurrence rate was significantly higher for diclofenac sodium 3% in comparison to imiquimod 5% cream (RR 1.10, 95% CI 1.02-1.1.8) and ranged from 10.6% for ingenol mebutate 0.015% gel to 23.5% for PDT. Few patients discontinued the trials due to adverse events. The results from the majority of the post-marketing surveillance studies deviated from those of pivotal trials.
CRIS-Team WoS Importer:2020-08-21

Autophagy in diabetic nephropathy: a review - Koch, Elias; Nakhoul, Rola; Nakhoul, Farid; Nakhoul, Nakhoul (International Urology and Nephrology, 2020)
Diabetes mellitus (DM) is the leading cause of end stage renal disease. 40% of the patients worldwide will require replacement therapy after 20 years of DM worldwide. Early-stage diabetic nephropathy is characterized by hyperfiltration related to hypeglycemia-induced afferent artery vasodilatation with micro-and macroalbuminuria. Later on, proteinuria with arterial hypertension may appear, culminating in glomerular filtration rate (GFR) decline and end stage renal disease. Forty percent of diabetic patients develop microvascular and macrovascular complications, with increased risk among patients with genetic predisposition, such as Haptoglobin 2–2 phenotype. The most frequent complications in the daily clinical practice are diabetic kidney disease, diabetic retinopathy and vascular disease, such as coronary artery disease and stroke. Various pathways are involved in the pathogenesis of diabetic kidney disease. Chronic systemic inflammation and the inflammatory response, such as increased circulating cytokines (Interleukins), have been recognized as main players in the development and progression of diabetic kidney disease. DM is also associated with increased oxidative stress, and alterations in carbohydrate, lipid and protein metabolism. Overexpression of the renin-angiotensin-aldosterone system (RAAS) in the kidney, the vitamin D-Vitamin D receptor-klotho axis, and autophagy. Differences in the ATG5 protein levels or ATG5 gene expression involved in the autophagy process have been associated with diabetic complications such as diabetic kidney disease. Under normal blood glucose level, autophagy is an important protective mechanism in renal epithelial cells, including podocytes, proximal tubular, mesangial and endothelial cells. Down regulation of the autophagic mechanism, as in hyperglycemic condition, can contribute to the development and progression of diabetic kidney disease.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Atg5; Autophagy; Diabetic nephropathy; Rapamune; Retinopathy; Sodium-glucose cotransporter inhibitors; Vitamin D

Chemical peelings for the treatment of actinic keratosis: a systematic review and meta-analysis - Steeb, Theresa; Koch, Elias; Wessely, A.; Wiest, L. G.; Schmitz, L.; Berking, Carola; Heppt, Markus (Journal of the European Academy of Dermatology and Venereology, 2020)
Background: Actinic keratosis (AK) is a common precancerous lesion of the skin that may be treated with chemical peelings. Despite their long-standing usage and clinical experience, no evidence-based recommendation regarding the efficacy and safety of chemical peelings for AK exists. Objectives: To systematically review and synthesize the current knowledge on chemically exfoliative peelings as interventions for AK. Methods: We performed a systematic literature research in Medline, Embase and CENTRAL and hand-searched pertinent trial registers for eligible records until 5 August 2019. Results from individual studies were pooled using a random-effects model or described in a qualitative synthesis. The risk of bias was estimated with the tools provided by the Cochrane Collaboration (randomized and non-randomized trials) and the Evidence Project (single-arm trials). Results: Four randomized controlled trials, two non-randomized controlled trials and two single-arm studies with a total sample size of n = 170 patients were included. Trichloroacetic acid (TCA) plus Jessner’s solution showed significantly lower participant complete clearance (RR 0.36, 95% CI: 0.14–0.90, two studies, I2 = 0%, P = 0.03) and lower lesion clearance (RR 0.92, 95% CI: 0.85–0.99, one study, P = 0.03) compared to 5-fluorouracil (5-FU) 5% cream. TCA as monotherapy showed lower lesion complete clearance (RR 0.75, 95% CI: 0.69–0.82, two studies, I2 = 7%, P < 0.001) and lower mean lesion reduction per patient compared to conventional photodynamic therapy (cPDT) (MD −20.48, 95% CI: −31.55 to −9.41, two studies, I2 = 43%, P = 0.0003). Pain was more pronounced in patients treated with cPDT in comparison with TCA (MD −1.71 95% CI: −3.02 to −0.41, two studies, I2 = 55%, P = 0.01). In the single-arm studies, 5-FU plus glycolic acid showed 92% lesion clearance and phenol peeling 90.6% participant complete clearance. All studies showed a high risk for bias. Conclusions: Future high-quality studies and a standardization of peeling protocols are warranted to determine the value of chemical peelings in the treatment of AK.
CRIS-Team Scopus Importer:2020-08-28

Clinical determinants of long-term survival in metastatic uveal melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Erdmann, Michael; Heinzerling, Lucie; Hohberger, Bettina; Knorr, Harald; Leiter, Ulrike; Meier, Friedegund; Mohr, Peter; Rahimi, Farnaz; et al. (Cancer Immunology, Immunotherapy, 2021)
This study aimed to identify prognostic factors in patients with metastatic uveal melanoma (UM) that were associated with long-term survival in a real-world setting. A total of 94 patients with metastatic UM were included from German skin cancer centers and the German national skin cancer registry (ADOReg). Data were analyzed for the response to treatment, progression-free survival, and overall survival (OS). Prognostic factors were explored with univariate Cox regression, log-rank, and χ2-tests. Identified factors were subsequently validated after the population was divided into two cohorts of short-term survival (< 2 years OS, cohort A, n = 50) and long-term survival (> 2 years OS, cohort B, n = 44). A poor ECOG performance status (hazard ratio [HR] 2.0, 95% confidence interval [CI] 1.0–3.9) and elevated serum LDH (HR 2.0, 95% CI 1.0–3.8) were associated with a poor OS, whereas a good response to immune checkpoint blockade (ICB, p < 0.001), radiation therapy (p < 0.001), or liver-directed treatments (p = 0.01) were associated with a prolonged OS. Long-term survivors (cohort B) showed a higher median number of organs affected by metastasis (p < 0.001), while patients with liver metastases only were more common in cohort A (40% vs. 9%; p = 0.002). A partial response to ICB was observed in 16% (12/73), being 21% (8/38) for combined ICB, 17% (1/6) for single CTLA4 inhibition, and 10% (3/29) for single PD1 inhibition. One complete response occurred in cohort B with combined ICB. We conclude that the response to ICB and the presence of extrahepatic disease were favorable prognostic factors for long-term survival.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Immune checkpoint blockade; Liver metastases; Liver-directed treatment; Long-term survival; Registry; Uveal melanoma

Clinical Prognostic Factors in metastatic Choroidal Melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, E.; Erdmann, Michael; Heinzerling, L.; Hohberger, Bettina; Knorr, H.; Leiter-Stoppke, U.; Meier, F.; Mohr, P.; Rahimi, F.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Conventional and three-dimensional photography as a tool to map distribution patterns of in-transit melanoma metastases on the lower extremity - Müller, Kilian; Berking, Carola; Voskens, Caroline; Heppt, Markus; Heinzerling, Lucie; Koch, Elias; Kramer, Rafaela; Merkel, Susanne; Schuler-Thurner, Beatrice; Schellerer, Vera; Steeb, Theresa; Wessely, Anja; et al. (Frontiers in Medicine, 2023)
Background: In melanoma, in-transit metastases characteristically occur at the lower extremity along lymphatic vessels. Objectives: The objective of this study was to evaluate conventional or three-dimensional photography as a tool to analyze in-transit metastasis pattern of melanoma of the lower extremity. In addition, we assessed risk factors for the development of in-transit metastases in cutaneous melanoma. Methods: In this retrospective, monocentric study first we compared the clinical data of all evaluable patients with in-transit metastases of melanoma on the lower extremity (n = 94) with melanoma patients without recurrence of disease (n = 288). In addition, based on conventional (n = 24) and three-dimensional photography (n = 22), we defined the specific distribution patterns of the in-transit metastases on the lower extremity. Results: Using a multivariate analysis we identified nodular melanoma, tumor thickness, and ulceration as independent risk factors to develop in-transit metastases ITM (n = 94). In patients with melanoma on the lower leg (n = 31), in-transit metastases preferentially developed along anatomically predefined lymphatic pathways. In contrast when analyzing in-transit metastases of melanoma on the foot (n = 15) no clear pattern could be visualized. In addition, no difference in distance between in-transit metastases and primary melanoma on the foot compared to the lower leg was observed using three-dimensional photography (n = 22). Conclusion: A risk-adapted follow-up of melanoma patients to detect in-transit metastases can be applied by knowledge of the specific lymphatic drainage of the lower extremity. Our current analysis suggests a more complex lymphatic drainage of the foot.
CRIS-Team Scopus Importer:2023-02-10
Keywords: 3D photography; in-transit metastasis; lower extremity; lymphatic pathways; melanoma

Gene network-based and ensemble modeling-based selection of tumor-associated antigens with a predicted low risk of tissue damage for targeted immunotherapy - Lischer, Christopher; Eberhardt, Martin; Flamann, Cindy; Berges, Johannes; Güse, Esther; Wessely, Anja; Weich, Adrian; Retzlaff, Jimmy; Dörrie, Jan; Schaft, Niels; Wiesinger, Manuel; März, Johannes; et al. (Journal for ImmunoTherapy of Cancer, 2024)
Background Tumor-associated antigens and their derived peptides constitute an opportunity to design off-the-shelf mainline or adjuvant anti-cancer immunotherapies for a broad array of patients. A performant and rational antigen selection pipeline would lay the foundation for immunotherapy trials with the potential to enhance treatment, tremendously benefiting patients suffering from rare, understudied cancers. Methods We present an experimentally validated, data-driven computational pipeline that selects and ranks antigens in a multipronged approach. In addition to minimizing the risk of immune-related adverse events by selecting antigens based on their expression profile in tumor biopsies and healthy tissues, we incorporated a network analysis-derived antigen indispensability index based on computational modeling results, and candidate immunogenicity predictions from a machine learning ensemble model relying on peptide physicochemical characteristics. Results In a model study of uveal melanoma, Human Leukocyte Antigen (HLA) docking simulations and experimental quantification of the peptide–major histocompatibility complex binding affinities confirmed that our approach discriminates between high-binding and low-binding affinity peptides with a performance similar to that of established methodologies. Blinded validation experiments with autologous T-cells yielded peptide stimulation-induced interferon-γ secretion and cytotoxic activity despite high interdonor variability. Dissecting the score contribution of the tested antigens revealed that peptides with the potential to induce cytotoxicity but unsuitable due to potential tissue damage or instability of expression were properly discarded by the computational pipeline. Conclusions In this study, we demonstrate the feasibility of the de novo computational selection of antigens with the capacity to induce an anti-tumor immune response and a predicted low risk of tissue damage. On translation to the clinic, our pipeline supports fast turn-around validation, for example, for adoptive T-cell transfer preparations, in both generalized and personalized antigen-directed immunotherapy settings.
CRIS-Team Scopus Importer:2024-05-24

Identifizierung von Biomarkern und neuen therapeutischen Zielen beim Aderhautmelanom - Wessely, Anja; Koch, Elias; Vera, Julio; Berking, Carola; Heppt, Markus (Journal der Deutschen Dermatologischen Gesellschaft, 2024)
Das Uveamelanom (UM) ist eine seltene Krebserkrankung, obwohl es der häufigste Tumor des Auges bei Erwachsenen ist. Die Patienten werden meist in Hautkrebszentren zur Behandlung der metastasierten Erkrankung vorgestellt. Es gibt jedoch erhebliche genetische, biologische und klinische Unterschiede zum kutanen Melanom. Die bei metastasiertem UM am häufigsten eingesetzten Therapien sind Tebentafusp und die kombinierte Immuncheckpoint-Blockade, die beide niedrige Ansprechraten aufweisen und mit hohen Behandlungskosten und erheblichen immunbedingten Toxizitäten verbunden sein können. Daher ist es von größter Bedeutung, einerseits Biomarker und klinische Profile zu identifizieren, die das Ansprechen auf die Behandlung vorhersagen können und andererseits neue therapeutische Ziele zu finden. Der Einsatz der Immuncheckpoint-Blockade zeigte in einer Reihe retrospektiver Studien günstigere Ergebnisse bei Patienten mit extrahepatischer Metastasierung und normalen Laktatdehydrogenase-Werten im Serum, so dass ihr Einsatz in dieser Subgruppe sinnvoller scheint. Um neue Zielmoleküle für Medikamente zu identifizieren, werden wir die Expression und Relevanz von Transkriptionsfaktoren der Neuralleiste in Bioproben von Patienten mit Next-Generation-Sequenzierung der dritten Generation analysieren. Computeralgorithmen und netzwerkbasierte Analysen werden die Identifizierung von Zielstrukturen für Medikamente erleichtern, die anschließend in Kurzzeit-Zellkulturen von Patienten validiert werden. Dieser Ansatz wird dazu beitragen, neue und personalisierte Behandlungen für das UM zu finde
CRIS-Team Scopus Importer:2024-01-19

Identifying biomarkers and novel therapeutic targets in uveal melanoma - Wessely, Anja; Koch, Elias; Vera, Julio; Berking, Carola; Heppt, Markus (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Uveal melanoma (UM) is an orphan cancer despite being the most common eye tumor in adults. Patients often present to skin cancer centers for treatment of metastatic disease although there are significant genetic, biological, and clinical differences from cutaneous melanoma. The treatments most commonly used for metastatic UM are tebentafusp and combined immune checkpoint blockade, both of which yield low response rates and may be accompanied by high treatment costs and significant immune-related toxicities. Thus, it is of paramount importance to identify biomarkers and clinical profiles predictive of treatment response and to find novel therapeutic targets. The use of immune checkpoint blockade showed more favorable outcomes in patients with extrahepatic disease and normal levels of serum lactate dehydrogenase in a panel of retrospective studies, making its use more reasonable in this subgroup. To identify novel drug targets, we will analyze the expression and relevance of neural crest transcription factors in patient bio-specimens using next-generation nanopore sequencing. Computer algorithms and network-based analysis will facilitate the identification of druggable targets which will subsequently be validated in patient-derived short-term cell cultures. This approach will help to find novel and personalized treatments for UM.
CRIS-Team Scopus Importer:2023-11-10

Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Patterns of Response and Survival According to the Presence of Hepatic and Extrahepatic Metastasis - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Hohberger, Bettina; Kaehler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; et al. (Cancers, 2021)
Simple Summary This retrospective multicenter study examines the influence of hepatic and extrahepatic metastases on the response of immune checkpoint blockade (ICB) in patients with metastatic uveal melanoma. A better response to dual ICB was observed in the presence of extrahepatic metastases in two recently published phase II trials. Therefore, we investigated two cohorts with and without extrahepatic metastasis and have assembled a population of 178 patients treated with ICB. The survival of this large cohort of patients with advanced UM was more favorable than that reported in previous benchmark studies. Patients with both hepatic and extrahepatic metastasis showed more favorable survival and higher response to dual ICB than those with hepatic metastasis only. Background: Since there is no standardized and effective treatment for advanced uveal melanoma (UM), the prognosis is dismal once metastases develop. Due to the availability of immune checkpoint blockade (ICB) in the real-world setting, the prognosis of metastatic UM has improved. However, it is unclear how the presence of hepatic and extrahepatic metastasis impacts the response and survival after ICB. Methods: A total of 178 patients with metastatic UM treated with ICB were included in this analysis. Patients were recruited from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of hepatic metastasis, two cohorts were compared: patients with liver metastasis only (cohort A, n = 55) versus those with both liver and extra-hepatic metastasis (cohort B, n = 123). Data were analyzed in both cohorts for response to treatment, progression-free survival (PFS), and overall survival (OS). The survival and progression probabilities were calculated with the Kaplan-Meier method. Log-rank tests, chi(2) tests, and t-tests were performed to detect significant differences between both cohorts. Results: The median OS of the overall population was 16 months (95% CI 13.4-23.7) and the median PFS, 2.8 months (95% CI 2.5-3.0). The median OS was longer in cohort B than in cohort A (18.2 vs. 6.1 months; p = 0.071). The best objective response rate to dual ICB was 13.8% and to anti-PD-1 monotherapy 8.9% in the entire population. Patients with liver metastases only had a lower response to dual ICB, yet without significance (cohort A 8.7% vs. cohort B 16.7%; p = 0.45). Adverse events (AE) occurred in 41.6%. Severe AE were observed in 26.3% and evenly distributed between both cohorts. Conclusion: The survival of this large cohort of patients with advanced UM was more favorable than reported in previous benchmark studies. Patients with both hepatic and extrahepatic metastasis showed more favorable survival and higher response to dual ICB than those with hepatic metastasis only.
CRIS-Team WoS Importer:2021-07-23

Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Re-Induction following Resistance or Toxicity - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Kähler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; et al. (Cancers, 2022)
Re-induction with immune checkpoint blockade (ICB) needs to be considered in many patients with uveal melanoma (UM) due to limited systemic treatment options. Here, we provide hitherto the first analysis of ICB re-induction in UM. A total of 177 patients with metastatic UM treated with ICB were included from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of ICB re-induction, two cohorts were compared: patients who received at least one ICB re-induction (cohort A, n = 52) versus those who received only one treatment line of ICB (cohort B, n = 125). In cohort A, a transient benefit of overall survival (OS) was observed at 6 and 12 months after the treatment start of ICB. There was no significant difference in OS between both groups (p = 0.1) with a median OS of 16.2 months (cohort A, 95% CI: 11.1–23.8) versus 9.4 months (cohort B, 95% CI: 6.1–14.9). Patients receiving re-induction of ICB (cohort A) had similar response rates compared to those receiving ICB once. Re-induction of ICB may yield a clinical benefit for a small subgroup of patients even after resistance or development of toxicities.
CRIS-Team Scopus Importer:2022-01-28
Keywords: CTLA-4; Immune checkpoint blockade; PD-1; Re-induction; Toxicity; Treatment resistance; Uveal melanoma

Is tebentafusp superior to combined immune checkpoint blockade and other systemic treatments in metastatic uveal melanoma? A comparative efficacy analysis with population adjustment - Petzold, Anne; Steeb, Theresa; Wessely, Anja; Koch, Elias; Vera, Julio; Berking, Carola; Heppt, Markus (Cancer Treatment Reviews, 2023)
Background: Distinct systemic treatments exist for metastatic uveal melanoma. Tebentafusp and combined immune checkpoint blockade (ICB) with ipilimumab plus anti-PD-1 antibodies are the most commonly used treatment options but their comparative efficacy is unclear. The aim of this study is to compare currently available systemic treatments regarding overall survival (OS) and progression-free survival (PFS) with a focus on the comparison of tebentafusp versus combined ICB. Methods: The protocol for this study was defined a priori and registered online in the PROSPERO international prospective register of systematic reviews (CRD42022308356, date of registration: 7.2.2022). We performed a systematic literature search in Medline, Embase, and Central to identify eligible studies reporting Kaplan-Meier curves or individual-level survival data showing OS and PFS for metastatic uveal melanoma patients treated with systemic treatments. Kaplan-Meier curves were digitized using the “WebPlotDigitizer” program. Individual-level survival data were subsequently remodelled and pooled for distinct treatment groups. To compare the OS of tebentafusp versus combined ICB, we used matching-adjusted indirect comparison (MAIC), two-stage MAIC (2SMAIC), and simulated treatment comparison (STC) together with digitized individual-level survival data as population-adjusted models. Results: Overall, 55 independent studies were included of which 2,682 patients were evaluable for OS and 2,258 for PFS. Tebentafusp showed the highest median OS (mOS) of 22.4 months (95% confidence interval (CI): 19.9–29.6) compared to combined ICB (mOS: 15.7 months (95% CI: 14.4–17.9)), anti-PD-(L)1 antibody (mOS: 10.9 months (95% CI: 9.8–13.4)), chemotherapy (mOS: 9.95 months (95% CI: 8.9–11.2)), targeted therapies (mOS: 8.86 months (95% CI: 7.5–10.8)), and anti-CTLA-4 antibody (mOS: 7.8 months (95% CI: 6.8–9.3). The median PFS (mPFS) was similar among the treatment groups ranging from 2.7 months to 3.4 months. For the comparison of tebentafusp versus combined ICB, the hazard ratio (HR) was 0.641 (95% CI: 0.449–0.915) in the unadjusted model, whereas the population-adjusted models showed a HR of 0.386 (95% CI: 0.236–0.631) using MAIC, 0.378 (95% CI: 0.234–0.612) applying 2SMAIC and 0.284 (95% CI: 0.184–0.440) using STC. Conclusions: Tebentafusp achieved the best results compared to combined ICB and other systemic treatments, although these results have to be interpreted with caution due to the approximative methodical approach and high heterogeneity of included studies.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Immune checkpoint blockade; Individual patient data; Population-adjusted models; Survival; Tebentafusp; Uveal melanoma

Liver-directed treatment is associated with improved survival and increased response to immune checkpoint blockade in metastatic uveal melanoma: results from a retrospective multicenter trial - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Eckstein, Markus; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; Loquai, Carmen; et al. (Frontiers of Medicine, 2023)
Metastases of uveal melanoma (UM) spread predominantly to the liver. Due to low response rates to systemic therapies, liver-directed therapies (LDT) are commonly used for tumor control. The impact of LDT on the response to systemic treatment is unknown. A total of 182 patients with metastatic UM treated with immune checkpoint blockade (ICB) were included in this analysis. Patients were recruited from prospective skin cancer centers and the German national skin cancer registry (ADOReg) of the German Dermatologic Cooperative Oncology Group (DeCOG). Two cohorts were compared: patients with LDT (cohort A, n = 78) versus those without LDT (cohort B, n = 104). Data were analyzed for response to treatment, progression-free survival (PFS), and overall survival (OS). The median OS was significantly longer in cohort A than in cohort B (20.1 vs. 13.8 months; P = 0.0016) and a trend towards improved PFS was observed for cohort A (3.0 vs. 2.5 months; P = 0.054). The objective response rate to any ICB (16.7% vs. 3.8%, P = 0.0073) and combined ICB (14.1% vs. 4.5%, P = 0.017) was more favorable in cohort A. Our data suggest that the combination of LDT with ICB may be associated with a survival benefit and higher treatment response to ICB in patients with metastatic UM.
CRIS-Team Scopus Importer:2023-07-21
Keywords: anti-CTLA-4; anti-PD-1; immune checkpoint blockade; liver-directed therapy; SIRT; uveal melanoma

Optimizing immune checkpoint blockade in metastatic uveal melanoma: exploring the association of overall survival and the occurrence of adverse events - Koch, Elias; Petzold, Anne; Dippel, Edgar; Erdmann, Michael; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Kähler, Katharina C.; Kreuzberg, Nicole; Leiter, Ulrike; Loquai, Carmen; et al. (Frontiers in Immunology, 2024)
Introduction: Despite recent advancements in the treatment of metastatic uveal melanoma (UM), the availability of further treatment options remains limited and the prognosis continues to be poor in many cases. In addition to tebentafusp, immune checkpoint blockade (ICB, PD-1 (+/-) CTLA-4 antibodies) is commonly used for metastatic UM, in particular in HLA-A 02:01-negative patients. However, ICB comes at the cost of potentially severe immune-related adverse events (irAE). Thus, the selection of patient groups that are more likely to benefit from ICB is desirable. Methods: In this analysis, 194 patients with metastatic UM undergoing ICB were included. Patients were recruited from German skin cancer sites and the ADOReg registry. To investigate the association of irAE occurrence with treatment response, progression-free survival (PFS), and overall survival (OS) two cohorts were compared: patients without irAE or grade 1/2 irAE (n=137) and patients with grade 3/4 irAE (n=57). Results: In the entire population, the median OS was 16.4 months, and the median PFS was 2.8 months. Patients with grade 3/4 irAE showed more favorable survival than patients without or grade 1/2 irAE (p=0.0071). IrAE occurred in 44.7% (87/194), and severe irAE in 29.4% (57/194) of patients. Interestingly, irColitis and irHepatitis were significantly associated with longer OS (p=0.0031 and p=0.011, respectively). Conclusions: This data may indicate an association between irAE and favorable survival outcomes in patients with metastatic UM undergoing ICB treatment and suggests that a reduced tolerance to tumor antigens could be linked to reduced tolerance to self-antigens.
CRIS-Team Scopus Importer:2024-06-28
Keywords: adverse events; CTLA-4; immune checkpoint blockade; immune-related; PD-1; toxicity; uveal melanoma

Poor Adherence to Self-Applied Topical Drug Treatment Is a Common Source of Low Lesion Clearance in Patients with Actinic Keratosis—A Cross-Sectional Study - Koch, Elias; Steeb, Theresa; Bender-Säbelkampf, Sophia; Busch, Dorothee; Feustel, Janina; Kaufmann, Matthias; Maronna, Andreas; Meder, Christine; Ronicke, Moritz; Toussaint, Frédéric; Wellein, Hedwig; Berking, Carola; et al. (Journal of Clinical Medicine, 2023)
Background: Many treatments for actinic keratosis (AK) have been proven efficient in clinical trials. However, patients with AK may still experience unsatisfactory therapeutic outcomes in clinical practice. Objectives: To investigate patient adherence to self-applied topical interventions for AK and to explore factors associated with adherence in a real-world setting. Methods: A cross-sectional study was conducted. Patients presenting with AK were asked to complete a self-administered questionnaire about their last topical AK treatment. Results: A total of 113 patients participated with a median age of 78.5 years (range 58–94). Fifty-four patients (47.8%) received topical diclofenac, ten (8.8%) imiquimod, nine (8%) 5-fluorouracil, nine (8%) 5-fluorouracil plus salicylic acid, and eight (7.1%) photodynamic therapy. The non-adherence rate was 46.9% (n = 53), and only 30.9% (n = 35) used the topical treatments according to the summary of product characteristics (SmPC). These subgroups were compared. Patients of the non-compliant group were significantly less informed about the application time of the specific topical intervention (p = 0.002) and adjusted the timeframe (p < 0.001) and application frequency of the therapy (p = 0.02) independently of their physician. Conversely, patients reporting a sufficient pre-treatment consultation (p = 0.019) generally complied with the SmPC compliance application. Conclusions: A thorough pre-treatment consultation can help to increase treatment adherence and ensure lesion clearance.
CRIS-Team Scopus Importer:2023-06-30
Keywords: actinic keratosis; adherence; compliance; consultation; topical treatment

Safety of topical interventions for the treatment of actinic keratosis - Koch, Elias; Wessely, Anja; Steeb, Theresa; Berking, Carola; Heppt, Markus (Expert Opinion on Drug Safety, 2021)
Introduction: Actinic keratosis (AK) are proliferations of atypical keratinocytes that may eventually progress to cutaneous squamous cell carcinoma. Therefore, AK requires consequent and early treatment. Areas covered: A variety of effective approaches is currently available for the clearance of AK. These interventions may be applied either in a lesion-directed or field-directed mode as AK can occur as single or multiple lesions. Field-directed approaches typically comprise topical drug-mediated interventions which aim at eliminating all visible lesions and also at clearing subclinical changes of the actinically damaged field. However, most treatment options are associated with local adverse events such as erythema, scaling, pain, and rarely with systemic symptoms. This expert review provides a comprehensive and up-to-date overview of the safety considerations of the commonly prescribed topical treatment agents cyclooxygenase inhibitors, 5-fluorouracil, imiquimod, ingenol mebutate, and photodynamic therapy. All these therapies have been proven efficient, yet they differ considerably regarding their safety profile. Expert opinion: In the future, safety concerns will relate to long-term and irreversible adverse drug events instead of application site reactions. In particular, the rate of treatment-associated non-melanoma skin cancers will increasingly come into focus and warrant investigation in postmarketing surveillance trials with a long-term follow-up.
CRIS-Team Scopus Importer:2021-08-06
Keywords: 5-fluorouracil; actinic keratosis; diclofenac; imiquimod; ingenol mebutate; photodynamic therapy

Standardized Computer-Assisted Analysis of PRAME Immunoreactivity in Dysplastic Nevi and Superficial Spreading Melanomas - Koch, Elias; Erdmann, Michael; Berking, Carola; Kiesewetter, Franklin; Kramer, Rafaela; Schliep, Stefan; Heppt, Markus (International Journal of Molecular Sciences, 2023)
PRAME (PReferentially expressed Antigen in MElanoma) is a cancer testis antigen that is frequently expressed in melanoma compared to benign melanocytic proliferations and nevi. However, the interpretation of the intensity and distribution of PRAME immunostaining is not standardized a lot, which makes interpretation difficult. PRAME-stained histological slides of superficial spreading melanomas (SSM) and dysplastic nevi (DN) were digitized and analyzed using the digital pathology and image platform QuPath. t-tests and ROC AUCs were performed with SPSS. A p-value of <0.05 was used for statistical significance, and a ROC AUC score of >0.8 was considered a good result. A cut-off score was defined in an evaluation cohort and subsequently analyzed in an independent validation cohort. In total, 81 PRAME-stained specimens were included. The evaluation cohort included 32 (50%) SSM and 32 (50%) DN, and the mean of PRAME-positive cells/mm2 for the entire lesion was 455.3 (SD 428.2) in SSM and 60.5 (SD 130.1; p < 0.001) in DN. The ROC AUC of PRAME-positive cells of the entire lesion was 0.866, and in the epidermis it was 0.901. The defined cut-off score to distinguish between DN and SSM was 97.67 cells/mm2. In the validation cohort, 16 out of 17 cases (94.1%) were correctly classified by the cut-off score. The computer-aided assessment of PRAME immunostaining is a useful tool in dermatopathology to distinguish between DN and SSM. Lesions with a moderate expression and indifferent morphologic features will remain a challenge for dermatopathologists.
CRIS-Team Scopus Importer:2023-04-21
Keywords: computer-assisted analysis; dysplastic nevus; immunohistochemistry; melanoma; PRAME

Step-by-step Improvement of mRNA-electroporated dendritic Cells in a Phase I / II Clinical Study in cutaneous Melanoma Patients: better Survival correlates with a higher Immunoscore and increased Expression of PEBP1 in the Blood - Dörrie, Jan; Schaft, Niels; Gross, S.; Ostalecki, Christian; Eberhardt, Martin; Vera-Gonzales, J.; Uslu, Ugur; Moreira, Alvaro; Koch, Elias; Kummer, Mirko; Erdmann, M.; Schliep, S.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

The Current State of Systemic Therapy of Metastatic Uveal Melanoma - Koch, Elias; Heppt, Markus; Berking, Carola (American Journal of Clinical Dermatology, 2024)
Uveal melanoma (UM) is genetically a distinct tumor compared to cutaneous melanoma (CM), and due to its low mutational burden, it is far less perceptible to the immune system. Thus, treatments that have revolutionized the treatment of CM remain widely inefficient in metastatic UM or only demonstrate effectiveness in a small subpopulation of patients. To this end, the therapeutic benefit of immune checkpoint blockade is very limited and may come at the expense of severe immune-related adverse events that could potentially affect all organ systems. Notably, tebentafusp, an entirely novel class of anti-cancer drugs, has received official authorization for the treatment of metastatic UM. It is the first agent that demonstrated a survival advantage in a randomized controlled trial of metastatic UM patients. Despite the survival benefit and approval, the restriction of tebentafusp to HLA-A*02:01-positive patients and the low objective response rate indicate the persistent need for additional therapies. Thus, liver-directed therapies are commonly used for tumor control of hepatic metastases and represent a central pillar of the daily management of liver-dominant disease. Further, promising data from targeted therapies independent of MEK-inhibitors, such as the combination of darovasertib and crizotinib, raise hope for additional options in metastatic UM in the future. This narrative review provides a timely and comprehensive overview of the current treatment landscape for metastatic UM.
CRIS-Team Scopus Importer:2024-06-28

Threshold Optimization for Tumor Markers S100b and MIA in Uveal Melanoma - A Single Center Analysis - Glaser, Naemi; Petzold, Anne; Wessely, Anja; Kaufmann, Matthias; Koch, Elias; Knorr, Harald; Voskens, Caroline; Heppt, Markus; Berking, Carola; Erdmann, Michael (Anticancer Research, 2023)
Background/Aim: Uveal melanoma (UM) is the most common malignant tumor of the eye in adults. Metastases develop in 50% of the patients, predominantly in the liver. In UM, the cut-off concentrations of the bloodbased tumor markers S100b and MIA are inconclusive. Patients and Methods: In this retrospective monocenter study, we statistically evaluated 1,878 S100b and 1,768 MIA measurements in 244 patients with UM from 2011-2020. Threshold optimization was performed using receiver operating characteristic (ROC) curves. Results: A total of 171 patients with non-metastatic UM (nmUM) and 73 patients with metastatic UM (mUM) showed no differences in sex, age at diagnosis or the affected eye. In mUM, 80% of the patients developed metastases to the liver at a median of 46 months after initial diagnosis. The sensitivity and specificity of S100b was 16.10% and 94.52%, and that of MIA was 31.86% and 81.42%, respectively. ROC curves revealed poor values for the area under the curve of 0.57 for S100b and 0.55 for MIA. The optimal cut-off concentration to detect metastases was 0.14 μg/l for S100b and 17.4 ng/ml for MIA. With at least one tumor marker elevated, optimized sensitivity was 20.40% and specificity 96.76%. Conclusion: Current thresholds for S100b and MIA in UM are not able to detect early metastatic disease and require additional diagnostics to clarify false positive results. Threshold optimization considering both S100b and MIA results in a better diagnostic validity with an acceptable specificity and a poor sensitivity. Highly sensitive blood-based and imaging methods to detect metastases early in UM are urgently needed.
CRIS-Team Scopus Importer:2023-11-03
Keywords: MIA; S100b; threshold optimization; tumor marker; Uveal melanoma